2014
DOI: 10.19044/elp.v1no1a6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Employee Retention in Ghana Commercial Bank, Kumasi

Abstract: The study investigated the determinants of employee retention in Ghana Commercial Bank (GCB), Kumasi. Various factors that contribute to employee retention such as organizational factors, human resource factors, organizational benefits, commitment, employees' retention and job satisfaction were examined. Quantitative research design, specifically a correlational design was used. Primary data were collected from 98 employees comprising senior and junior staff, through questionnaire administration. The data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Human resource management practices are gaining more importance, with the passage of time these are becoming equally important in the organizations because employees are considered as the most imperative asset of the organization (Anis et al, 2011). Hence, there is a need to foster the demands of the employees which actually boost their motivation level to avoid turnover (Enu-Kwesi et al, 2014). The concept of retention gained importance in the early 1970s with the rise in the origination of SME's as competitive employers, leading to the provision of sustainable employment opportunities (Coff, 1997).…”
mentioning
confidence: 99%
“…Human resource management practices are gaining more importance, with the passage of time these are becoming equally important in the organizations because employees are considered as the most imperative asset of the organization (Anis et al, 2011). Hence, there is a need to foster the demands of the employees which actually boost their motivation level to avoid turnover (Enu-Kwesi et al, 2014). The concept of retention gained importance in the early 1970s with the rise in the origination of SME's as competitive employers, leading to the provision of sustainable employment opportunities (Coff, 1997).…”
mentioning
confidence: 99%
“…The existence of multicollinearity could affect the results for the path significance (Enu-Kwesi, Koomson, Segbenya, and Annan-Prah, 2014), and for that matter, the presence of multicollinearity was checked, and the results are presented in Table 4. The results revealed that the inner values obtained using the variance inflated factors (VIF) as suggested by Hair et al (2017) were below the maximum threshold of 3.30 as suggested by (Hair et al (2017).…”
Section: Results and Findingsmentioning
confidence: 99%
“…On the other hand in African Counties, Reddy & Govender, [6] indicated that "retention factors like challenging work, flexible working plans, opportunities for learning and development as well as remuneration were adopted at a leading South African bank to retain employees". Similarly, Enu-Kwesi & Koomson, [7] point out that training and development stood out as significant employee retention factors at the Ghana Commercial Bank in Ghana.…”
Section: Introductionmentioning
confidence: 99%